Kecerdasan Emosi dan Hubungannya dengan Pencapaian Akademik - Norhayati, Haji Ahmad Zakaria (2003)
The purpose of this study is to identify KDPM semester 3 students’ Emotional Intelligence. Another purpose of this study is also to identify the correlations between students’ Emotional Intelligence and academic achievements. 224 students from KDPM semester 3 IPDA of different courses were being selected as the respondents. Questionnaire which were adapted from Tapia’s (1998) and Moon’s (1996) were being used as tools for this study. Data were analyzed descriptively and correlatively using SPSS Win Verse 11.5 programmed to gain the frequency, percentage, mean, standard deviation and Pearson Correlation. The result of this study showed that the level of self-awareness consciousness and empathy domain are at the highest rank. Meanwhile the level of self-regulation consciousness, motivations and social skills domain are at the medium rank. Results also showed that there are significant relations between KDPM semester 3 IPDA students’ Emotional Intelligence and academic achievements. There are also positive relations between self-awareness domain, self-regulation and motivation with students’ academic achievements.